Fragments historiques d’une université à distance canadienne francophone : l’Université TÉLUQ - Entretien avec Michel Umbriaco - Papi, Cathia (Médiations et médiatisations, 2021)
In this interview, Michel Umbriaco, who participated in the founding of Université TÉLUQ, presents the context that gave birth to the university and some of the elements that marked its evolution. He explains that created in the early 1970s to make education more accessible; this university has gone through a succession of great successes and crises that have even called its existence into question. After reviewing the half-century of experience of the Université TÉLUQ, he discusses its future and the conditions for its continued existence in the context of higher education in Quebec and Canada.
Number: 6
Keywords: Québec; enseignement supérieur; formation à distance; histoire; technologies éducatives